Child Sexual Abuse by Catholic Priests, Deacons, and Male Members of Religious Orders in the Authority of the German Bishops' Conference 1946–2014. (April 2021) - Dressing, Harald; Dölling, Dieter; Hermann, Dieter; Kruse, Andreas; Schmitt, Eric; Bannenberg, Britta; Whittaker, Konrad; Hoell, Andreas; Voss, Elke; Salize, Hans Joachim
This study explores the extent of sexual abuse of minors by members of the Catholic Church in Germany. It is the first comprehensive study to examine this extent in a European country. The goals of this study are as follows: (a) to analyze whether the extent and characteristics of sexual abuse in a European country are comparable to those in the United States and Australia and (b) how discrepancies can be explained. The personnel files of 38, 156 Catholic Priests, deacons, and male members of religious orders in the authority of the German Bishops' Conference were analyzed. The study period lasted from 1946 to 2014. All 27 German dioceses took part in this study. A total of 4.4% of all clerics ( N = 1, 670) from 1946 to 2014 were alleged to have committed sexual abuse, and 3, 677 children or adolescents were identified as victims. These results are similar to those from comparable studies in the United States. Sexual abuse of minors within the authority of the Catholic Church seems to be a worldwide phenomenon.